2009
DOI: 10.1526/003601109789037268
|View full text |Cite
|
Sign up to set email alerts
|

Rural‐Urban Differences in Environmental Concern in Canada

Abstract: Distinctions between rural and urban populations are well documented in environmental sociology literature. Rural and urban places may exert different influences on participation in environmentally supportive behavior (ESB) as well as on other forms of environmental concern (EC). The influence of these distinct geographies may be due to present circumstances or because of childhood socialization in these places. Using data from a national survey in Canada (n51 664), we use cognitive (basic values, environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
117
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 38 publications
11
117
3
6
Order By: Relevance
“…Overall levels of engagement in energy use reduction were found to be similar between urban and non-urban residents, in line with previous findings for other types of environmental engagement (Huddart-Kennedy et al, 2009). However, it was found that concern for climate change is a more important factor for urban residents than for rural residents, suggesting that further research into the effect of location should consider how attitudes affect behaviours in different areas, rather than just considering whether the attitudes are similar, as is typically done www.ccsenet.org/eer Energy and Environment Research Vol.…”
Section: Energy Use Reductionsupporting
confidence: 90%
See 4 more Smart Citations
“…Overall levels of engagement in energy use reduction were found to be similar between urban and non-urban residents, in line with previous findings for other types of environmental engagement (Huddart-Kennedy et al, 2009). However, it was found that concern for climate change is a more important factor for urban residents than for rural residents, suggesting that further research into the effect of location should consider how attitudes affect behaviours in different areas, rather than just considering whether the attitudes are similar, as is typically done www.ccsenet.org/eer Energy and Environment Research Vol.…”
Section: Energy Use Reductionsupporting
confidence: 90%
“…The prioritisation placed by respondents on climate change was expected to have a direct effect on behaviour (Huddart-Kennedy et al, 2009;Whitmarsh & O'Neill, 2010), however this study found that it only indirectly correlated with home energy use reduction through environmental identity and concern for climate change. The difference could be due to variable construction, as respondents were not directly asked to prioritise climate change relative to other issues.…”
Section: Energy Use Reductioncontrasting
confidence: 68%
See 3 more Smart Citations